2007
DOI: 10.1007/s12028-007-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Reliability of the Ramsay Scale

Abstract: Based on these findings, there is insufficient evidence to support the reliability of the Ramsay scale as a measure of sedation assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…All clinical sedation scales suffer from several weaknesses - they are highly subjective, and some of the commonly used scales, such as the Ramsay scale [62] suffer from significant inter-rater variability [63]. In addition most clinical sedation scales were designed for a different population than the one in our study.…”
Section: Methodsmentioning
confidence: 99%
“…All clinical sedation scales suffer from several weaknesses - they are highly subjective, and some of the commonly used scales, such as the Ramsay scale [62] suffer from significant inter-rater variability [63]. In addition most clinical sedation scales were designed for a different population than the one in our study.…”
Section: Methodsmentioning
confidence: 99%
“…31,60,94,95 The first reliability study was completed in the late 1990s after the original study had been published, and observed a high inter-rater reliability (Ä w = .88, p < .001). While Olson et al 74 reported low inter-rater reliability, subsequent weighted kappa assessments demonstrated similarly high inter-rater reliability levels ranging from .85 to .94. 40,55 Initial construct validity of the RSS was first demonstrated by Carrasco et al 56 when comparing it with the Newcastle Sedation Scale.…”
Section: Discussionmentioning
confidence: 92%
“…38 Concern has been raised however that the levels of sedation described are not clear or mutually exclusive. 74,91 Despite these concerns in the literature, the RSS was found to be a common sedation-scoring instrument in Europe, 18 North America, 92 Australia and New Zealand ICUs. 93 However, a more recent study 90 examining Australia and New Zealand ICUs did not report the RSS commonly in use.…”
Section: Discussionmentioning
confidence: 99%
“…We used this system because a Ramsay sedation scale is not adjustable and is insufficient as a measure of sedation assessment [16]; if patients were anxious or restless or both, then they scored 1-2; if they were cooperative, orientated and calm, 3-4; if they responded to commands, 5-6; if they gave a brisk response to stimuli, 7-8; if they responded only sluggishly or could not make any response to stimuli, 9-10. Patients' characteristics (age, weight, baseline heart and respiratory rates, SpO 2 and BP), ASA physical status and morphine consumption, as well as the number of patients with an indwelling urinary catheter of more than 24 h, time of first getting out of bed after the operation and hospitalization days after surgery were compared with two-way analysis of variance (ANOVA).…”
Section: Methodsmentioning
confidence: 99%